Effect of Dietary Supplementation of Synthetic and Natural b-Carotene on Survival, Growth and Pigmentation in Freshwater Ornamental Koi (Cyprinus carpio L.) Carp - Kaur, S.; Kaur, V.I.; Holeyappa, S.A.; S.O. Khairnar, S.O. Khairnar (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted to assess the efficacy of synthetic and natural b-carotene (through dried carrot powder) incorporated @ 25 and 50 ppm each with respect to survival, growth and pigmentation in freshwater ornamental koi (Cyprinus carpio L.) carp fish for 90 days. Five diets were prepared including control (D1) without carotenoid source and four others supplemented with 25 (D2) and 50 ppm (D3) of syntheticb-carotene and 25 (D4) and 50 ppm (D5) of natural b-carotene, respectively. Fish growth in term of NWG (g), % NWG, PER, SGR and condition factor was maximum in group D4 (2.66, 92.00, 0.09, 0.71 and 1.60) and minimum in group D5 (0.90, 31.6, 0.05, 0.29 and 1.14). Colouration studies indicated higher (P